Visible light-triggered disruption of micelles of an amphiphilic block copolymer with BODIPY at the junction - Patil, Naganath G.; Basutkar, Nitin B.; Ambade, Ashootosh V. (Chemical Communications, 2015)
A visible light-cleavable polymer is synthesised to overcome the limitations of UV-sensitive polymers. Photocleavable BODIPY functionalized with an ATRP initiator and alkyne was used to obtain an amphiphilic block copolymer by conducting the click reaction and polymerization simultaneously. Micellar assembly of the polymer was disintegrated under visible light irradiation with controlled release of cargo.

Visible light and pH-responsive star copolymer and doxorubicin-polymer conjugate micelles for combination drug delivery and bioimaging - Basutkar, Nitin B.; Surapaneni, Sai Geetika; Alam, Md. Shafi; Ambade, Ashootosh V. (Journal of macromolecular science part A- pure and applied chemistry, 2024)
Amphiphilic 3-arm star copolymer containing visible light-cleavable BODIPY group and pH-responsive imine bonds at the junction of hydrophilic poly(ethylene glycol) (PEG) and two poly(epsilon-caprolactone) (PCL) arms was synthesized by the combination of ring-opening polymerization (ROP) and click chemistry. The formation and stimuli-responsive disruption of micelles were analyzed using dynamic light scattering and transmission electron microscopy. Dual stimuli-responsive release of anticancer drugs Doxorubicin (Dox) and Camptothecin (CPT) from the micelles was studied. Micellar assemblies containing Dox conjugated to PEG-BODIPY through imine bonds were prepared and controlled release of Dox in response to visible light and pH was shown. CPT and Dox-loaded star copolymer micelles as well as CPT loaded Dox-conjugated micelles were used in cellular uptake studies on MDA-MB 231 cells, and the synergistic effect of the two stimuli on the release of the two drugs was demonstrated inside the cells. Micellar assemblies also showed excellent bioimaging properties in the cellular uptake studies. [GRAPHICS]
Keywords: BODIPY; drug conjugate; micelles; pH-responsive; visible light-responsive

Visible light-responsive composition-dependent morphology and cargo release in mixed micelles of dendron amphiphiles - Avhad, Shankarrao V.; Kumar, Sugam; Ambade, Ashootosh V. (Langmuir, 2025)
2,2-Bis-(methylol)propionic acid-based second-generation polyester dendron amphiphile (T-D) containing visible light-responsive donor-acceptor Stenhouse adduct (DASA) as hydrophobic tails is synthesized. Micelles of T-D amphiphile and its mixed micelles of varying compositions with nonresponsive dendron amphiphile containing lauryl groups are prepared in aqueous solution. In transmission electron microscopy and atomic force microscopy analyses, T-D amphiphiles show rice grain-like ellipsoidal micelles as the predominant morphology. Mixed micelles display a composition-dependent morphology gradient such that the morphology changes from rice grain like to mixed to completely spherical with decreasing content of the T-D amphiphile. Complete morphology change to spherical micelles and partial reversal to ellipsoidal micelles, finally leading to ill-defined aggregates, are observed when the T-D amphiphile micelles are subjected to visible light-dark storage photoswitching cycles. Small-angle neutron scattering (SANS) analysis of 1 wt.% micellar solution in THF:water (10:90) reveals only a minor change in shape and size upon photoirradiation, and the data could be fitted to spherical or ellipsoidal model. Release of hydrophobic dye from mixed micelles is tuned by the content of the photoresponsive amphiphile. Cellular uptake and visible light-triggered release of hydrophobic drug from mixed micelles are demonstrated using MDA-MB-231 cells, suggesting their applicability for photoresponsive drug delivery.